Plant Immune System Activation Upon Citrus Leprosis Virus C Infection Is Mimicked by the Ectopic Expression of the P61 Viral Protein - Arena, Gabriella D.; Ramos-González, Pedro Luis; Falk, Bryce W.; Casteel, Clare L.; Freitas-Astúa, Juliana; Machado, Marcos A. (Frontiers in Plant Science, 2020)
Citrus leprosis virus C (CiLV-C, genus Cilevirus, family Kitaviridae) is an atypical virus that does not spread systemically in its plant hosts. Upon its inoculation by Brevipalpus mites, only localized lesions occur, and the infection remains limited to cells around mite feeding sites. Here, we aimed to gain insights into the putative causes of viral unfitness in plants by expanding the limited knowledge of the molecular mechanisms underlying plant/kitavirid interactions. Firstly, we quantified the CiLV-C viral RNAs during the infection in Arabidopsis thaliana plants using RT-qPCR and systematized it by defining three stages of distinguishing subgenomic and genomic RNA accumulation: i) 0–24 h after infestation, ii) 2–4 days after infestation (dai), and iii) 6–10 dai. Accordingly, the global plant response to CiLV-C infection was assessed by RNA-Seq at each period. Results indicated a progressive reprogramming of the plant transcriptome in parallel to the increasing viral loads. Gene ontology enrichment analysis revealed the induction of cell growth-related processes at the early stages of the infection and the triggering of the SA-mediated pathway, ROS burst and hypersensitive response (HR) at the presymptomatic stage. Conversely, infected plants downregulated JA/ET-mediated pathways and processes involved in the primary metabolism including photosynthesis. Marker genes of unfolded protein response were also induced, suggesting a contribution of the endoplasmic reticulum stress to the cell death caused by the viral infection. Finally, we transiently expressed CiLV-C proteins in Nicotiana benthamiana plants to undertake their roles in the elicited plant responses. Expression of the CiLV-C P61 protein consistently triggered ROS burst, upregulated SA- and HR-related genes, increased SA levels, reduced JA levels, and caused cell death. Mimicry of responses typically observed during CiLV-C–plant interaction indicates P61 as a putative viral effector causing the HR-like symptoms associated with the infection. Our data strengthen the hypothesis that symptoms of CiLV-C infection might be the outcome of a hypersensitive-like response during an incompatible interaction. Consequently, the locally restricted infection of CiLV-C, commonly observed across infections by kitavirids, supports the thesis that these viruses, likely arising from an ancestral arthropod-infecting virus, are unable to fully circumvent plant defenses.